MODEL INKLUSI KEUANGAN PADA UMKM BERBASIS PEDESAAN - Irmawati, Setyani; Damelia, Delu; Puspita, Dita Wahyu (JEJAK: Jurnal Ekonomi dan Kebijakan, 2013)
In general, regional economy is supported by micro, small and medium enterprises (SMEs). They have important role in promoting economic growth in Indonesia. In Indonesia, there are various types of SMEs that are spreadout throughout the region, one of which is batik SMEs. Klaten regency has the largest number of Batik SMEs in Central Java province. Commonly, the issue of SMEs in general is the problem of capital. To overcome this issue, there is a model named âFinancial Inclusionâ to encourage the financial system to be accessible by society. The purpose of this study is to identify the application of financial inclusion in rural-based batik SMEs in Klaten regency and analyze its strengths, weaknesses, opportunities, and obstacles in the implementation of financial inclusion in the SME. Data analysis technique used is descriptive analysis and SWOT analysis. The results revealed that the form of the model of financial inclusion for SMEs Batik in Klaten regency is financial institutions in terms of capital. This is in the form of low interest loans and KUR (Business Credit fo Society). Then, there is a provision of assistance from financial institutions. In terms of marketing, it is necessary for SMEs in having intensive assistance, participating in batik exhibition and advertisement. Having applied this model, it is expected that SMEs Batik Klaten will be well-improved.Â Perekonomian daerah pada umumnya ditopang oleh Usaha Mikro Kecil dan Menengah (UMKM). Perannya sangat vital dalam meningkatkan pertumbuhan ekonomi di Indonesia. Di Indonesia terdapat berbagai jenis UMKM yang tersebar diseluruh wilayah, salah satunya adalah UMKM batik. Kabupaten Klaten memiki jumlah UMKM batik terbanyak di provinsi Jawa Tengah. Persoalan UMKM pada umumnya adalah masalah permodalan. Untuk mengatasinya terdapat satu model bernama âInklusi Keuanganâ yang dapat mendorong sistem keuangan agar dapat diakses seluruh lapisan masyarakat. Tujuan penelitian ini adalah mengidentifikasi penerapan inklusi keuangan pada UMKM batik berbasis perdesaan di Kabupaten Klaten serta menganalisis kekuatan, kelemahan, peluang, dan hambatan dalam penerapan inklusi keuangan pada UMKM tersebut. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis SWOT. Hasil yang diperoleh yaitu model inklusi keuangan untuk UMKM Batik di Kabupaten Klaten yaitu masuknya lembaga keuangan dalam segi permodalan yaitu berbentuk kredit bunga rendah dan KUR, yang selanjutnya dilakukan pendampingan dari lembaga keuangan. Sedangkan dari segi pemasaran, diperlukan adanya pendampingan intensif, pengikutsertaan pameran batik serta advertisement. Dengan model tersebut, diharapkan akan terbentuk UMKM Batik Klaten yang berkualitas.